Next generation sequencing for preimplantation genetic testing of blastocysts aneuploidies in women of different ages - Krzysztof Lukaszuk; Grzegorz Jakiel; Waldemar Kuczynski; Sebastian Pukszta; Joanna Liss; Lukasz Plociennik; Aron Lukaszuk; Ewa Pastuszek (Annals of Agricultural and Environmental Medicine, 2015)
Most of the current preimplantation genetic screening of aneuploidies tests are based on the low quality and low density comparative genomic hybridization arrays. The results are based on fewer than 2,700 probes. Our main outcome was the association of aneuploidy rates and the women’s age. Between August–December 2013, 198 blastocysts from women (mean age 36.3+-4.6) undergoing in vitro fertilization underwent routine trophectoderm biopsy. NGS was performed on Ion Torrent PGM (Life Technologies). The results were analyzed in five age groups ( 40). 85 blastocysts were normal according to NGS results. The results in the investigated groups were (% of normal blastocyst in each group): 40 (38.5%). Our study suggests that NGS PGD is applicable for routine preimplantation genetic testing. It allows also for easy customization of the procedure for each individual patient making personalized diagnostics a reality.